2020
DOI: 10.3390/su12124960
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Computing Usage in SMEs. An Empirical Study Based on SMEs Employees Perceptions

Abstract: This paper aims to determine the perception of small and medium-sized enterprises (SMEs) employees regarding the usage of cloud computing services in their activities. The quantitative study was conducted on a sample of 315 respondents employed in Romanian SMEs. Testing of the conceptual model was performed with the WarpPLS 3.0 software. The study aimed to test how several constructs—the perceived benefits, disadvantages and risks, communication process, overall experience of using cloud computing services, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…an empirical study of on SMEs employees perceptions about cloud computing identified the following factors: the perceived benefits, disadvantages and risks, communication process, overall experience of using cloud computing services, perceived image, and empathy regarding the cloud computing services. [20] different determinants of e-service quality are proposed by [21]: "e-service quality has incubative and active dimensions for increasing hit rates, stickiness, and customer retention. The incubative dimension consists of: ease of use, appearance, linkage, structure and layout, and content.…”
Section: Analysis Of the Survey Resultsmentioning
confidence: 99%
“…an empirical study of on SMEs employees perceptions about cloud computing identified the following factors: the perceived benefits, disadvantages and risks, communication process, overall experience of using cloud computing services, perceived image, and empathy regarding the cloud computing services. [20] different determinants of e-service quality are proposed by [21]: "e-service quality has incubative and active dimensions for increasing hit rates, stickiness, and customer retention. The incubative dimension consists of: ease of use, appearance, linkage, structure and layout, and content.…”
Section: Analysis Of the Survey Resultsmentioning
confidence: 99%
“…A cloudbased environment eliminates the need for SMEs to employ and retain IT staff for managing the ERP. These systems need less upfront investment and SMEs only pay for the cloud services based on their use [95]. Therefore, the cloud ERP technology is typically more effective for SMEs as it provides benefits of low implementation, licensing and support costs, fast implementation processes and increased agility, facilitating these companies to change and adjust to the organizational and market requirements.…”
Section: Adoption Of Cloud Erp In Smesmentioning
confidence: 99%
“…The most pressing issue is the non-availability of data, both in terms of necessary volume and qualitative expressiveness (lack of labeled faults). Financial resources to provide adequate sensory equipment and big data management plays some role, and the employment of cloud solutions to manage adequate high-capacity data transfer is increasingly accepted for use, primary as found by the 2020 survey [73].…”
Section: A Data Resourcesmentioning
confidence: 99%